Kepekaan Ekologis dan Kesenjangan Kawasan Taman Hutan Raya (Tahura) Kota Palangka Raya, Provinsi Kalimantan Tengah : Ecological Sensitivity and Regional Disparities in the Forest Park (Tahura) of Palangka Raya City, Central Kalimantan Province - Yulianto, Santosa; Arianto, Rahmad Ade; Librawan, Roma; Noor, Yunani Hamlin; Yulianti, Reri (HUTAN TROPIKA, 2024)
The Ecological Sensitivity Level of Tahura Area of Palangka Raya City is dominated by Very Sensitive (76.81%) which indicates that this part of the area has high biodiversity potential with its unique biogeophysical ecosystem, so serious efforts and attention are needed to protect and preserve it. Land use intervention in the Tahura area is dominated (57.98%), indicating the high intervention of human activities in the form of land use in this part of the area. The gap level of Tahura Area is dominated by Very Sensitive, Land Use Intervention (39.87%). This indicates that this part of the Tahura Area has a very high ecological sensitivity and is vulnerable to intensive human activity intervention, resulting in a very high risk of damage to its natural ecosystem. While the level of gap in the Very Sensitive, No Land Use Intervention area (36.94%) indicates that this part of the Tahura Area has very high ecological sensitivity and relatively minimal human intervention, and is at low risk of damage to its natural ecosystem. Based on this, the ecological sensitivity and gap of the Palangka Raya City Forest Park (Tahura) area indicates the vulnerability of the area to high intervention of human activities and the risk of damage to natural ecosystems, as well as the loss of biodiversity if no immediate mitigation and rehabilitation measures are taken, as well as proper planning and governance of the area